European Reports: Energy in Europe. (4th August 2014) - Waeterloos, Christian; Fee, Derek; Kestner, Mathew; Jahn, Andreas; Krawinkel, Holger; Gowen, Michael; Delehanty, Miriam
The following reports are abstracted from 'Energy in Europe' published by the Commission of the European Communities. They contain: 'Why a European energy charter?' by Christian Waeterloos; 'Specific actions for vigorous energy efficiency (SAVE)' by Derek Fee; 'First energy efficiency directives under SAVE programme' by Mathew Kestner; 'Least–cost planning for Schleswig–Holstein' by Andreas Jahn, and Holger Krawinkel; 'OPETS: Organisations for the Promotion of Energy Technology' by Michael Gowen; 'Regional and urban energy planning in the EC' from the DG XVII, Task Force on Community Integration; Accompanying Measures Unit; and 'EC–Mexico energy cooperation ' by Miriam Delehanty.